'Another Day to Swing on Clothes Lines': The Bee Gees and Australia. (24th March 2017) - O'Grady, Pat
Abstract : A large proportion of overseas-born artists comprise the pop music industries in Australia. Keith Urban, Rick Springfield, members of Cold Chisel, The Angels and Masters Apprentices, for example, not only represent themselves as 'Australian;' they are frequently associated with the nation by critics and audiences. The Bee Gees also exemplify this trend. In this article, I wish to bring into focus The Bee Gees' curious connection with Australia. In order to do this task, I ask a series of questions; first, what is The Bee Gees connection to Australia? Second, how has this connection been constructed and continually reinforced? Third, what forms of discursive resistance against their 'Australianness' exist in regard to these constructions? And finally, how might we critically understand the tensions that have emerged regarding their legitimacy as an 'Australian band'? I argue that their connection to Australia is continually renegotiated due in large part to their incompatibility with dominant performances of masculinity by Australian white male musicians.